Bentuk Penyajian Tari Jepin Gerangkang Kelurahan Batu Layang Kecamatan Pontianak Utara - Ulhasanah, Nida; Ismunandar, Ismunandar; Tindarika, Regaria (CV. ITTC INDONESIA, 2024)
Jepin Gerangkang Dance, Batu Layang Village, North Pontianak District, Pontianak City. The method used is a qualitative descriptive choreographic approach. Data in the form of observation techniques, interviews, and documentation. The Jepin Gensgkang dance has 3 variations, namely the beginning, core and ending. This dance can be danced by men or women. Musical instruments used are selodang, beruas, tambourine, drum, accordion, and violin. Women's clothing is baju kuning, cloth with gill patterns, and Malay lotus. Teluk belanga men's clothing, cloth with gill pattern, and cloth with gill pattern. The makeup used by dancers is realistic makeup without changing the character of the face.